2023
DOI: 10.2106/jbjs.22.01193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Total Hip Arthroplasty and Hemiarthroplasty for Femoral Neck Fracture

Abstract: Background: The optimal treatment of older patients with a displaced femoral neck fracture remains a controversial topic. This study aimed to compare clinical outcomes across a matched group of patients with a femoral neck fracture treated with either hemiarthroplasty or total hip arthroplasty (THA).Methods: Routinely collected health-care databases were linked to create a population-based cohort of 49,597 patients ‡60 years old from Ontario, Canada, who underwent hemiarthroplasty or THA for a femoral neck fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These risks of dislocation are consistent with data from the more recent RCTs showing rates of <5%. Similarly, 2 population-based studies from Canada found dislocation rates of <2% for THA and HA in the treatment of femoral neck fracture 18,39 . Both of these studies demonstrated that THA was associated with an increased risk of dislocation despite the low rates-similar to our own findings 18,39 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…These risks of dislocation are consistent with data from the more recent RCTs showing rates of <5%. Similarly, 2 population-based studies from Canada found dislocation rates of <2% for THA and HA in the treatment of femoral neck fracture 18,39 . Both of these studies demonstrated that THA was associated with an increased risk of dislocation despite the low rates-similar to our own findings 18,39 .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, 2 population-based studies from Canada found dislocation rates of <2% for THA and HA in the treatment of femoral neck fracture 18,39 . Both of these studies demonstrated that THA was associated with an increased risk of dislocation despite the low rates-similar to our own findings 18,39 . In contrast, a population-based analysis from France, in which dual-mobility implants were utilized in 18% of the procedures in the THA group, demonstrated that THA was associated with a reduced risk of dislocation, despite having found a dislocation rate of 5.9% in the THA group 19 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations